IMPLEMENTATION OF LITERACY STRATEGIES IN OVERCOMING STUDENTS READING DIFFICULTIES IN ELEMENTARY SCHOOL - Rosya Arumi Zuharo; Fathoni, Achmad (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The basic skills that learners need to master are literacy skills. Generally, children in elementary school age tend to have problems when learning such as reading. The purpose of this study is to describe (1) How the literacy strategy is implemented in overcoming reading difficulties of grade III B students at SDN Sondakan No 11 Surakarta. (2) What factors are influential in implementing the literacy strategy. This study used descriptive qualitative research methods. As a data collection technique, the researcher used interview, observation, and documentation techniques. The data analysis technique applied was interactive analysis. The data validity technique used was triagulation of techniques and sources. The results showed that, (1) The implementation of literacy reading and writing strategies involving the observe, read and write back method, reading corners, student seating arrangements and sticking texts and pictures on the classroom wall was effective enough to be applied in overcoming reading difficulties of elementary school students. (2) The inhibiting factor in the implementation of this literacy strategy is the less than optimal coordination of students due to the low concentration of students while learning, while the supporting factors are the availability of support from the environment and facilities as well as positive cooperation with parents.